Wall properties and heat transfer analysis of the peristaltic motion in a power‐law fluid. (15th February 2012) - Hayat, T.; Javed, M.; Asghar, S.; Hendi, A. A.
SUMMARY A mathematical analysis has been carried out to investigate the effect of elasticity of the flexible walls on the peristaltic flow of a power‐law fluid. The heat transfer analysis is further examined. Expressions of stream function, velocity, and temperature distributions are presented in closed form under long wavelength and low Reynolds number approximations. The effects of the various parameters entering into the mathematical analysis are sketched and discussed. Copyright © 2012 John Wiley & Sons, Ltd.